2020
DOI: 10.1021/acsapm.0c00790
|View full text |Cite
|
Sign up to set email alerts
|

Nanocellulose and Elastin Act as Plasticizers of Electrospun Bioinspired Scaffolds

Abstract: In this work, we produced cross-linked electrospun hybrid scaffolds composed of gelatin/poly-d,l-lactide (PDLLA), gelatin/PDLLA/nanocellulose, and gelatin/PDLLA/cellulose nanocrystals/elastin. Fourier-transform infrared spectroscopy, X-ray diffraction, and high-performance liquid chromatography demonstrated the complete embedding of each component in the hybrid scaffolds. The degree of cross-linking was quantified by the 2,4,6-trinitrobenzenesulfonic acid assay, and attenuated total reflectance spectroscopy re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 101 publications
0
26
0
Order By: Relevance
“…HFP, known for its low nucleophilicity and strong hydrogen bond‐donating ability, [40] was chosen as solvent because of its ability to solubilize both PDLLA polymer and El peptides [10b] . Herein, HFP was mixed together with H 2 O, to dissolve HA, derivatives 2 and 3 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…HFP, known for its low nucleophilicity and strong hydrogen bond‐donating ability, [40] was chosen as solvent because of its ability to solubilize both PDLLA polymer and El peptides [10b] . Herein, HFP was mixed together with H 2 O, to dissolve HA, derivatives 2 and 3 .…”
Section: Resultsmentioning
confidence: 99%
“…[9] Recently, we have obtained electrospun scaffolds by co-electrospinning and blending elastin-derived peptides with other natural or synthetic materials, such as gelatin, poly-D,L-lactide and nanocellulose crystals (CNCs). [10] Besides, the natural polymer HA has been widely used in biomaterial synthesis. [11] HA is a non-sulfated polysaccharide composed of D-glucuronic acid (GlcA) and N-acetyl-D-glucosamine (GlcNAc), linked by alternating β-1!3 and β-1!4 glycosidic bonds, resulting in 4)-β-GlcA-(1!3)-β-GlcNAc-(1!…”
Section: Introductionmentioning
confidence: 99%
“…Uniaxial tensile testing of the scaffold in the dry state, previously described (Ciarfaglia et al), showed that addition of 8% of CNC, both in the presence and absence of elastin peptide reduced significantly Young's moduli, thus increasing elasticity, while in the hydrated state no differences were observed. Interestingly, 8NGPk and El8NGPk scaffolds showed higher elongation at break inferring a role as plasticizer in the dry state 55 …”
Section: Resultsmentioning
confidence: 97%
“…A promising approach is skin tissue engineering which is to incorporate appropriate living cells, biochemical and physical factors, and tissue engineering scaffolds to create tissue-like structures for skin repair. The tissue engineering scaffolds are a key element to support the tissue reconstruction and are required to imitate the extracellular matrices (ECMs) morphologically and chemically . The protein-based ultrafine fibrous scaffolds are therefore favored because they have not only a semblable architecture as the fine fibers in ECMs but also a similar hydrophilic nature and amino acid composition which facilitate cell accommodation and prevention of dehydration.…”
Section: Introductionmentioning
confidence: 99%
“…The tissue engineering scaffolds are a key element to support the tissue reconstruction and are required to imitate the extracellular matrices (ECMs) morphologically and chemically. 5 The protein-based ultrafine fibrous scaffolds are therefore favored because they have not only a semblable architecture as the fine fibers in ECMs but also a similar hydrophilic nature and amino acid composition which facilitate cell accommodation and prevention of dehydration. Besides, the fibrous structure with interconnected pores guarantees the exchange of oxygen and nutrients and the removal of metabolic wastes.…”
Section: Introductionmentioning
confidence: 99%